Kansui-liquorice enhances the “water-expelling” effect of Gansui Banxia decoction in rats with malignant ascites by targeting the NPs/NPRs/cGMP/PKGⅡ pathway and T cell immunity - Huo, Min; Liu, Haiyan; Chen, Shaohong; Xiu, Lingling; Yu, Xue; Zhong, Gansheng (Frontiers in Pharmacology, 2025)
Ethnopharmacological relevanceThe combination of Euphorbia kansui Liou ex S.B.Ho (kansui) and Glycyrrhiza uralensis Fisch (liquorice) is contraindicated in Chinese medicine, but whether it can be used in clinical practice remains controversial. The classic formula, Gansui Banxia decoction (GBD), contains kansui and liquorice, which is effective in treating an abnormal accumulation of body fluids, such as malignant ascites (MA); however, the contraindications of kansui and liquorice have limited its clinical application.Aim of the studyThis study aims to provide a theoretical basis for the rational application of kansui-liquorice by investigating its role and mechanism in GBD.Materials and methodsLC-MS/MS was used to detect the metabolic differences of - glycyrrhetinic acid, glycyrrhizic acid, glycyrrhizin, glycyrrhizin, glycyrrhizin terpinolipid A, and paeoniflorin - in the liquid of MA rats before and after taking GBD. Network pharmacology was employed to predict the potential targets and mechanisms of GBD in the treatment of MA. The experimental validation was still using MA rats as a model. Flow cytometry was used to assess the expression of immune cells in blood and ascites, and the proliferation and development of T cells in bone marrow and thymus. Elisa was used to detect the content of atrial natriuretic peptide (ANP) and brain natriuretic peptide (BNP) in blood. Western blot and qRT-PCR were used to detect the expression of NPs/NPR-A/cGMP/PKG II pathway-related gene and proteins in kidney. The MA model was established by intraperitoneal injection of walker-256 cells at a concentration of 2 × 106/mL and an injection volume of 1 mL. The model was successfully established when the abdominal cavity was obviously distend and touched with a water-shaking sound, and ascites could be seen after opening the abdominal cavity.ResultsWe confirmed that GBD containing kansui-liquorice could promote the metabolism of liquorice and reduce the precipitation of toxic substances (kansuinine A). It may also target cellular immunity to exert a drug effect. Further experimental verification found that GBD containing kansui-liquorice could promote the activation of the NPs/NPRs/cGMP/PKGⅡ pathway and exert a diuretic effect in MA rats. Besides that, it could increase the proportion of CD8CD28 T cells, reduce the proportion of immune-suppressing cells, and maintain the stability of the developmental environment of the T cells.ConclusionWe believe that kansui and liquorice are important components of GBD, and their combination could promote GBD to promote the clinical remission of MA through direct (activation of the NPs/NPRs/cGMP/PKGⅡ pathway) and indirect (regulating T-cell immunity) water-expelling effects.